4 - New Frontiers of Exclusion: Private Higher Education and Women's Opportunities in Kenya: Ibrahim Ogachi Oanda - Ibrahim Ogachi Oanda, (Journal of Higher Education in Africa, 2005)
fhe semi-privatisation of public universities and the growth ofprivate universities have been two important developments affecting higher education iri Kenya in the last decade. The trend towards the privatisation ofuniversity education has been in tune with global neo-liberal policies that Kenya embraced from 1986. The policies were promoted for their potential to broaden opportunities for previously excluded groups. In higher education, private universities and programmes claim to offer more opportunities for women and a higher transition from college to employment. A close analysis however reveals that these claims are of limited validity. Rather than expanding opportunities for women, private universities in Kenya tend to cre ate new subtle arenas for exclusion. This article analyses the ways in which the logic and practical working of private universities accentuate women's marginalisation in terms of access policies, academic cultures and disciplinary orientations.